Synthesis and Application of Breadfruit Peel-Based Magnetic Activated Carbon for Pb(II) Removal from Electroplating Wastewater - Kartika Udyani; Dian Yanuarita Purwaningsih; Nurul Kurnia Putri (Journal of Applied Sciences, Management and Engineering Technology, 2025)
The electroplating industry is one of the producers of liquid waste containing lead heavy metal (Pb(II)) which is a high risk to the environment and human health. Pb(II) metal is a toxic heavy metal, does not decompose easily, is bioaccumulative, and its solubility is strongly influenced by pH. In acidic conditions, Pb is more easily soluble as Pb²⁺ ions, in alkaline conditions it can form deposits such as Pb(OH)₂. Based on its toxic and persistent nature, Pb needs to be treated before wastewater is discharged into the environment. This study aims to process electroplating liquid waste through the development of magnetic activated carbon based on breadfruit bark synthesized using the precipitation method, as well as to examine the effectiveness of its application in the removal of Pb(II) ions from electroplating liquid waste. The characterization of magnetic activated carbon as an adsorbent is carried out using various analysis techniques to determine the surface morphology, pore structure, and specific surface area. Adsorption tests were performed to evaluate the effect of contact time, and adsorbent dose on Pb(II) removal. The results showed that magnetic activated carbon has a high ability to absorb Pb(II), with a removal of 96.79%. the optimal conditions were obtained at an adsorbent mass of 3.424 g and a contact time of 79.137 minutes, with a prediction of Pb(II) removal of 98.083%